Pengembangan Persamaan Regresi Kenyamanan Termal Ruang Luar Untuk Situasi Malam Hari Di Daerah Tropis Lembab - Sangkertadi Sangkertadi; Reny Syafriny; Cynthia E V Wuisang (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
In tropical and humid cities, at night human activities also take place at outdoor space under the open sky, especially around 18.00 to 22.00. Air temperature during that time also tends to be warm, and the humidity has started to increase. The question is how much the thermal comfort level of people at outdoor space so that they feel enjoy and productive for their activities. Through this study, two regression equations was developed in order to predict the level of human thermal comfort at outdoor spaces at night in tropical area. A total of 80 adults consisting of 40 men and 40 women as subjects and respondents have filled out questionnaire about the perception of thermal comfort scales when obtaining various climate penetrations. The respondents wore tropical clothing types. The experiment was carried out at outdoor under open sky at coastal area in the city of Manado. The climate variables include air temperature, humidity, and wind speed. The regression equation consists of two, namely for the case of activities sitting with light work, and walking leisurely. The equation is in the form of Y=f(Xi), where Y is the scale of perception of comfort, and Xi is the climate variable. The equation produces a predicted range of perception of thermal comfort in terms of numbers 2 (feeling hot), 1 (feeling a slightly hot), 0 (feeling comfortable), -1 (feeling a slightly cold), and -2 (feeling cold). The R value of the two regression equations are 0.7. One of the results of calculations by using the regression shows that at outdoor spaces, pepole who sit with light work still feel comfortable in a climatic environment with air temperature 320C, humidity 65%, and being touched by a wind speed of 1 m/s.